Một số vấn đề về văn hóa hiện nay - Đinh, Thị Hằng (Dạy và học ngày nay, 2023)
In the context of innovation and international integration, our country's education and training industry has invested a lot of money and intelligence to find an appropriate direction to improve the quality of training in Vietnam. But, in the end, education reform is only successful when we build a standard and healthy school culture, in a specific school culture space.